First round of external quality assessment of dengue diagnostics in the WHO Western Pacific Region, 2013 - Kwoon Yong Pok; Raynal C Squires; Li Kiang Tan; Tomohiko Takasaki; Sazaly Abubakar; Futoshi Hasebe; Jeffrey Partridge; Chin Kei Lee; Janice Lo; John Aaskov; Lee Ching Ng; Frank Konings (World Health Organization Regional Office for the Western Pacific, 2015)
Objective: Accurate laboratory testing is a critical component of dengue surveillance and control. The objective of this programme was to assess dengue diagnostic proficiency among national-level public health laboratories in the World Health Organization (WHO) Western Pacific Region. Methods: Nineteen national-level public health laboratories performed routine dengue diagnostic assays on a proficiency testing panel consisting of two modules: one containing commercial serum samples spiked with cultured dengue viruses for the detection of nucleic acid and non-structural protein 1 (NS1) (Module A) and one containing human serum samples for the detection of anti-dengue virus antibodies (Module B). A review of logistics arrangements was also conducted. Results: All 16 laboratories testing Module A performed reverse transcriptase polymerase chain reaction (RT-PCR) for both RNA and serotype detection. Of these, 15 had correct results for RNA detection and all 16 correctly serotyped the viruses. All nine laboratories performing NS1 antigen detection obtained the correct results. Sixteen of the 18 laboratories using IgM assays in Module B obtained the correct results as did the 13 laboratories that performed IgG assays. Detection of ongoing/recent dengue virus infection by both molecular (RT-PCR) and serological methods (IgM) was available in 15/19 participating laboratories. Discussion: This first round of external quality assessment of dengue diagnostics was successfully conducted in national-level public health laboratories in the WHO Western Pacific Region, revealing good proficiency in both molecular and serological testing. Further comprehensive diagnostic testing for dengue virus and other priority pathogens in the Region will be assessed during future rounds.